KORELASI ANTARA KOMUNIKASI INTERPERSONAL DALAM LINGKUNGAN KELUARGA DENGAN PERILAKU MORAL SISWA DI SDN SURYODININGRATAN 3 - Wijayanti, Dwi; Pratomo, Wachid (Universitas Sarjanawiyata Tamansiswa, 2021)
The research was conducted to know how effective family interpersonal relationships are to student moral behavior. This research is correlation research with the number of sample 24 students. The data collecting technique used a closed questionnaire formed rating scale. The instrument validity test used product-moment and the reliability test used Alpha Cronbach formulation. The data analysis technique used normality and linearity test. The hypothesis test used a double linear regression test. The result of the research is there is a positive correlation between family interpersonal relationships to student moral behavior SDN Suryodiningratan 3 Yogyakarta with the correlation between interpersonal communications system in the family environment (X) and student moral behavior (Y) with correlation coefficient in the amount of 0,321 (p<0,05), so that sum of interpersonal communication variable contribution in the family environment to student moral behavior is 32,1% while the rest is the external variable factor. Thus it is gotten a research conclusion that communication system applied family environment influenced highly to moral behavior changes for a student so that it needs to be increased communication intensity between children and parents or all family members.